Addressing the Shortage of Geriatricians: What Medical Educators Can Learn From the Nurse Practitioner Training Model. (September 2015) - Golden, Adam G.; Silverman, Michael A.; Issenberg, S. Barry
Abstract : Physicians' career interest in geriatric medicine continues to wane at a time when the health care needs of older adults are increasing. Nurse practitioners have helped fill the U.S. physician gap by delivering outpatient care to older adults and can practice with full autonomy in many states. Nursing graduate school programs are preparing adult-gerontology primary care nurse practitioners to successfully deliver outpatient care services using a model of training with fewer requirements that is more flexible and of shorter duration compared with the training model for geriatricians. Nurse practitioners can also obtain initial certification and recertification with less time commitment and at lower cost than geriatricians. Whether the outpatient care provided by nurse practitioners is comparable to the care provided by physicians remains a subject of debate. However, as nurse practitioners' scope of practice expands, the perception exists that the outpatient clinical roles of adult-gerontology primary care nurse practitioners and geriatricians are similar. This raises questions about whether there are too many educational and certification requirements for geriatricians. The authors encourage medical educators to learn from the success of the nurse practitioner education model for training large numbers of primary care providers. They propose decreasing the duration of medical school and graduate medical education training for geriatricians and providing educational debt repayment programs as potential incentives to stimulate career interest in geriatric medicine.